THE DEVELOPMENT PRINCIPLES OF MODERN KARAKALPAK LYRICS IN POETRY COMPOSITION (World Bulletin of Social Sciences, 2024)
The fact that the composition of a lyrical work is a component of a general literary composition is substantiated by summarizing theoretical ideas about literary composition, the difference and characteristics of the composition of a lyrical work from the composition of other literary types, the forms of conveying the content of lyrical works, the compositional units related to the content, the issue of internal composition, the delivery of content in poetry along with compositional forms, as auxiliary internal compositional components, dream, landscape, as well as types of lyrical words: monologue, dialogue, author's words, inserted (vstavnoy) verses, division of the poem into verses and stanzas, types of stanzas, rhyming order, with the structure of the poem such as the number of syllables related qualities, together with the paragraph, which is considered the main component in the external compositional structure of the lyric work: the preface, dedication, epigraph, footnote, artistic units related to the content of a number of poems, but graphically separated from the general text, were analyzed on the example of the current Karakalpak lyric and an appropriate conclusion was drawn.